(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A substantial corpus of study has been conducted to investigate the several ways in which design may contribute to the success of a company. For instance, in order to support and leverage their attempts to innovate, organizations often look to design for assistance and support when they are attempting to develop new goods, services, processes, models, and strategies. But to what extent do academics agree on how the link between design and innovation should be defined? Is there any way to explain what the relationship between the two is supposed to be? In this essay, we analyze whether the design literature that has been produced over the last thirty years has an answer to these issues. Specifically, we look at the design literature that has been published in the United Kingdom. We organize our findings into clusters that describe the key roles that design activity plays in the innovation process, how designers personally play a part, and the internal and external factors that contribute to design/innovation associations. These clusters are organized according to the following: We also offer the idea that design language, whether it is visual, methodological, or procedural, has become not just an organizational principle that supports creative endeavors, but it has also become the language of innovation itself. This is something that we think is important to recognize.